2021
DOI: 10.1186/s12348-021-00251-5
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Vogt-Koyanagi-Harada disease under control for more than 6 years, following anti-SARS-CoV-2 vaccination

Abstract: Background/purpose Vogt-Koyanagi-Harada (VKH) disease is a primary stromal choroiditis with bilateral granulomatous panuveitis. If initial-onset VKH is treated early and relentlessly the disease can be controlled and even “cured” in a substantial number of cases. We are reporting on a patient treated early and in a sustained fashion who was inflammation free for seven years but who presented a reactivation 6 weeks after the second dose of anti-SARS-CoV-2 vaccination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 18 publications
1
68
1
1
Order By: Relevance
“… A case series of numerical imbalance in incidences of Bell’s palsy between vaccine and placebo arms during trials BNT162b2, mRNA-1273 NA NA n = 7 Papasavvas et al . 33 Reactivation of Vogt-Koyanagi-Harada disease under control for more than 6 years, following anti-SARS-CoV-2 vaccination. A case report of reactivation of Vogt-Koyanagi-Harada disease post-vaccination BNT162b2 2 6 weeks Photophobia, ocular pain n = 1 Phylactou et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… A case series of numerical imbalance in incidences of Bell’s palsy between vaccine and placebo arms during trials BNT162b2, mRNA-1273 NA NA n = 7 Papasavvas et al . 33 Reactivation of Vogt-Koyanagi-Harada disease under control for more than 6 years, following anti-SARS-CoV-2 vaccination. A case report of reactivation of Vogt-Koyanagi-Harada disease post-vaccination BNT162b2 2 6 weeks Photophobia, ocular pain n = 1 Phylactou et al .…”
Section: Resultsmentioning
confidence: 99%
“…was identified. 33 The reported subject was a woman with a pre-existing diagnosis of VKH well controlled for the past six years. The initial onset of VKH was severe, necessitating infliximab infusions which were continued as regular maintenance therapy.…”
Section: Amnmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the need for ophthalmological studies on vaccine-related side-effects, where SARS-CoV-2 vaccination may become annual. Known intraocular side-effects include acute macular neuroretinopathy, central serous chorioretinopathy, reactivation of Vogt-Koyanagi-Harada disease, panuveitis, Descemet’s membrane endothelial keratoplasty (DMEK) graft rejection, retinal hemorrhage and vascular events including retinal arterial occlusion and retinal vein occlusion (RVO) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Here, we present a unique case series of RVO, and age-related macular degeneration (AMD) exhibiting submacular hemorrhage, temporally related to administration of SARS-CoV-2 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Reactivation of Vogt-Koyanagi-Harada (VKH) Disease Papasavvas et al reported that a 40-year-old female taking infliximab for VKH disease for six years had reactivation six weeks after the second dose of BNT162b2 COVID-19 vaccine. On examination, AC inflammation, mutton-fat KPs, retinal folds, subretinal fluid, and increased choroidal thickness were noted [27].…”
mentioning
confidence: 99%